The influence of childhood IQ and education on social mobility in the Newcastle Thousand Families birth cohort - Forrest Lynne F; Hodgson Susan; Parker Louise; Pearce Mark S (BMC, 2011)
Abstract Background It has been suggested that social, educational, cultural and physical factors in childhood and early adulthood may influence the chances and direction of social mobility, the movement of an individual between social classes over his/her life-course. This study examined the association of such factors with intra-generational and inter-generational social mobility within the Newcastle Thousand Families 1947 birth cohort. Methods Multivariable logistic regression was used to examine the potential association of sex, housing conditions at age 5 years, childhood IQ, achieved education level, adult height and adverse events in early childhood with upward and downward social mobility. Results Childhood IQ and achieved education level were significantly and independently associated with upward mobility between the ages of 5 and 49-51 years. Only education was significantly associated (positively) with upward social mobility between 5 and 25 years, and only childhood IQ (again positively) with upward social mobility between 25 and 49-51 years. Childhood IQ was significantly negatively associated with downward social mobility. Adult height, childhood housing conditions, adverse events in childhood and sex were not significant determinants of upward or downward social mobility in this cohort. Conclusions As upward social mobility has been associated with better health as well as more general benefits to society, supportive measures to improve childhood circumstances that could result in increased IQ and educational attainment may have long-term population health and wellbeing benefits.